Localizing and Theorizing Speech/Rhetoric Studies in the Philippine University - Tatcho, Orville B. (Philippine Humanities Review; Vol 25 No 1: Philippine Humanities Review (2023-2024): Rebyu ng Arte at Literatura ng Pilipinas, 2025)
This essay aims to provide a roadmap for the speech communication discipline, as I offer recommendations that apply not only to the speech communication track of the University of the Philippines Baguio, the context in which I operate, but also more generally to the contemporary state of the speech communication discipline in the Philippines. The first part of the essay discusses four arguments to approach the study of speech (used interchangeably with rhetoric here): (1) anchor speech through interdisciplinary perspectives, (2) reconceptualize speech as a theoretical subject and not just a practical one, (3) reimagine and situate speech in the socio-cultural tradition in Robert Craig’s paradigms of communication theory, and (4) employ a mixed-methods approach to studying speech/rhetoric. For the latter part of the essay, I propose the thesis as a concrete project where students, with the guidance of their faculty advisers, may explore the possibilities and recommendations for speech/rhetoric studies. I provide concrete examples of topics that can be pursued and, where necessary, I cite some of my own publications and the work of other scholars not as models of scholarship but as starting points for what can be done when theorizing speech/rhetoric. While some of the suggestions in this essay are not entirely novel, they aim to study speech from a more nuanced, locally grounded, and theoretically informed position which I believe is the challenge of 21st century speech/rhetoric education.